Ekspertni sistem za nadzor kota upogibanja na numerično krmiljeni upogibni stiskalnici - Jovišević, Vid (Strojniški vestnik, 2005)
This paper treated develop expert system ES-APKANT which gives higher accuracy and better quality of metal bending process and guarantee achievement of demanded metal bending angle in first bending operation. The paper shows model of hydraulic bending press PSE 135/3000, which is suitable for implementation of expert system, structure of press numerical control system and description of expert system for bending process control. Expert system ES-APKANT is verified on the example of C45U sheet metal bending.
Keywords: sistemi ekspertni; stiskalnice; upogibanje pločevine; krmiljenje numerično; ekspertni sistemi